Assessing viability and infectivity of foodborne and waterborne stages (cysts/oocysts) of Giardia duodenalis, Cryptosporidium spp., and Toxoplasma gondii: a review of methods - Rousseau Angélique; La Carbona Stéphanie; Dumètre Aurélien; Robertson Lucy J.; Gargala Gilles; Escotte-Binet Sandie; Favennec Loïc; Villena Isabelle; Gérard Cédric; Aubert Dominique (Parasite, 2018)
Giardia duodenalis, Cryptosporidium spp. and Toxoplasma gondii are protozoan parasites that have been highlighted as emerging foodborne pathogens by the Food and Agriculture Organization of the United Nations and the World Health Organization. According to the European Food Safety Authority, 4786 foodborne and waterborne outbreaks were reported in Europe in 2016, of which 0.4% were attributed to parasites including Cryptosporidium, Giardia and Trichinella. Until 2016, no standardized methods were available to detect Giardia, Cryptosporidium and Toxoplasma (oo)cysts in food. Therefore, no regulation exists regarding these biohazards. Nevertheless, considering their low infective dose, ingestion of foodstuffs contaminated by low quantities of these three parasites can lead to human infection. To evaluate the risk of protozoan parasites in food, efforts must be made towards exposure assessment to estimate the contamination along the food chain, from raw products to consumers. This requires determining: (i) the occurrence of infective protozoan (oo)cysts in foods, and (ii) the efficacy of control measures to eliminate this contamination. In order to conduct such assessments, methods for identification of viable (i.e. live) and infective parasites are required. This review describes the methods currently available to evaluate infectivity and viability of G. duodenalis cysts, Cryptosporidium spp. and T. gondii oocysts, and their potential for application in exposure assessment to determine the presence of the infective protozoa and/or to characterize the efficacy of control measures. Advantages and limits of each method are highlighted and an analytical strategy is proposed to assess exposure to these protozoa.